Advancing alcohol research in low-income and middle-income countries: a global alcohol environment framework. Issue 4 (16th April 2020) - Walls, Helen; Cook, Sarah; Matzopoulos, Richard; London, Leslie
Abstract : Alcohol-related harm has gained increased attention in high-income countries (HICs) in recent years which, alongside government regulation, has effected a reduction in alcohol consumption. The alcohol industry has turned its attention to low-income and middle-income country (LMIC) markets as a new source of growth and profit, prompting increased consumption in LMICS. Alcohol use in LMICs is also increasing. There is a need to understand particularly in LMICs the impact of industry strategy in shaping local contexts of alcohol use. We draw on conceptualisations from food systems research, and research on the commercial determinants of health, to develop a new approach for framing alcohol research and discuss implications for alcohol research, particularly in LMICs, focusing on South Africa as an illustrative example. We propose a conceptualisation of the 'alcohol environment' as the system of alcohol provision, acquisition and consumption—including, critically, industry advertising and marketing—along with the political, economic and regulatory context of the alcohol industry that mediates people's alcohol drinking patterns and behaviours. While each country and region is different in terms of its context of alcohol use, we contrast several broadly distinct features of alcohol environments in LMICs and HICs. Improving understanding of the full spectrum of influences on drinking behaviour, particularly in LMICs, is vital to inform the design of interventions and policies to facilitate healthier environments and reduce the harms associated with alcohol consumption. Our framework for undertaking alcohol research may be used to structure mixed methods empirical research examining the role of the alcohol environment particularly in LMICs.